Theoretical, Manufacturing and Clinical Application Aspects of a Prostate Brachytherapy I-125 Source in Brazil - Zeituni, Carlos A.; Souza, Carla D.; Moura, Eduardo S.; Sakuraba, Roberto Kenji; Rostelato, Maria Elisa C.M.; Feher, Anselmo; Moura, João A.; Somessari, Samir; Costa, Osvaldo L. (IntechOpen, 2012)
None